Graphic Warning Labels Affect Hypothetical Cigarette Purchasing Behavior among Smokers Living with HIV - Pacek, Lauren R. (Int J Environ Res Public Health, 2019)
Cigarette pack graphic warning labels (GWLs) are associated with increased knowledge of tobacco-related harms; scant research has evaluated their effects on behavior among vulnerable populations. We used a behavioral economic approach to measure the effects of GWLs and price on hypothetical cigarette purchasing behavior among HIV-positive smokers. Participants (n = 222) completed a cigarette valuation task by making hypothetical choices between GWL cigarette packs at a fixed price ($7.00) and text-only warning label cigarette packs at increasing prices ($3.50 to $14.00; $0.25 increments). More than one-quarter (28.8%) of participants paid more to avoid GWLs. The remaining participants’ purchasing decisions appear to have been driven by price: 69.8% of participants chose the cheaper pack. Across all participants, overall monetary choice value observed for GWL cigarette packs (mean = $7.75) was greater than if choice was driven exclusively by price ($7.00). Most (87.4%) preferred the text-only warning label when GWL and text-only cigarette packs were equally priced. Correlation analysis indicated GWL pack preference was associated with agreement with statements that GWLs would stop individuals from having a cigarette or facilitate thoughts about quitting. These data suggest that GWLs may influence some HIV-positive smokers in such a way that they are willing to pay more to avoid seeing GWLs.